Using automated grammar processing programs in teaching- arabic language- automated parsing ( BelArabi )as a model - hadjebar, radia; Boudjenah, hayat (El Omda in Linguistics and Discourse Analysis, 2025)
structures. we downloaded the arabic automated parsing program and selected some compositions contained in the tutorial for beginners and then presented to the automated parsing program to find that the program has the ability to determine the correct expression of different types of words in the sentence, but this program must be updated.